Effects of low-level laser therapy on the healing of foot ulcers in people with diabetes mellitus - Albuquerque Brandão, Maria Girlane Sousa; Ximenes, Maria Aline Moreira; Ramalho, Aline de Oliveira; Veras, Vivian Saraiva; Barros, Lívia Moreira; Araújo, Thiago Moura de (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: Identify the effects of low-level laser therapy on the healing of diabetic foot. Method: Systematic review of the PubMed, LILACS, SciELO, CINAHL, Cochrane, Web of Science and Scopus databases, in which 92 articles were identified and six were included in the final sample after the eligibility criteria. Results: The articles pointed out as effects of laser therapy the effectiveness in the progression of the tissue repair process of the diabetic foot, pain relief, anti-inflammatory action, increased tissue perfusion of the lesion and improvement of the vascular response and the nervous system. Conclusion: Laser is an adjuvant therapy that can accelerate the wound healing process, relieve pain, improve neovascularization, and thus minimize the risk of complications, such as lower limb amputation and improvement of quality of life for people with diabetes and impaired skin integrity.